Graphical User Interface Optimalization Based C# with Visual Studio to Operator Control Unit Rhino Robot - Tata Tanjung Tamara; Achmad Affandi; Imam Arifin; M. Fajar Adityo (Institut Teknologi Sepuluh Nopember, 2019)
System of communication and data storage on the old version Graphical User Interface (GUI) can not developed or modified because it is not made in a modular way. In addition, the memory capacity is quite large because there are XNA Framework function and excessive robot control menus. Based on these problems we need to optimize GUI on the Operator Control Unit (OCU) Rhino robot. Programming language using C # with Integrated Development Environment (IDE) Visual Studio. Communication systems and data storage robots are grouped into 3 parts of the program with inheritance class. It creation use one of the IDE features of the Windows Presentation Foundation (WPF). The result of this research is program of communication system and data storage more structured so that can be developed for further research. After that, the memory capacity of the new version of GUI is 57.4 MB with an average memory usage of about 513.5 MB and the number of GUI pages as many as 8 with 3 main page details and 5 supporting pages to control robot motion.